2015
DOI: 10.1631/jzus.b1500160
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of oral tea polyphenols and Lactobacillus brevis M8 on biochemical parameters, digestive enzymes, and cytokines expression in broilers

Abstract: This study investigates the long-term effects of oral tea polyphenols (TPs) and Lactobacillus brevis M8 (LB) on biochemical parameters, digestive enzymes, and cytokines expression in broilers. In experiment 1, 240 broiler chickens were selected to investigate the effects of 0.06 g/kg body weight (BW) TP and 1.0 ml/kg BW LB on broilers; in experiment 2, 180 broiler chickens were assigned randomly to three groups to investigate the effects of different dosages of TP (0.03, 0.06, and 0.09 g/kg BW) combined with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…With regard to potential effects of polyphenols on inflammation in broilers, only one study is available so far. That study investigated the effect of tea polyphenols (0.03–0.09 g/kg body weight) on the expression of various proinflammatory cytokines (IL‐1B, IL‐4, IL‐6, IL‐10, TNF, IFN‐γ) in the intestine of broilers (Li et al., ). It was found that most of these genes were downregulated by tea polyphenols.…”
Section: Effects Of Polyphenols On Oxidative Stress and Inflammation mentioning
confidence: 99%
“…With regard to potential effects of polyphenols on inflammation in broilers, only one study is available so far. That study investigated the effect of tea polyphenols (0.03–0.09 g/kg body weight) on the expression of various proinflammatory cytokines (IL‐1B, IL‐4, IL‐6, IL‐10, TNF, IFN‐γ) in the intestine of broilers (Li et al., ). It was found that most of these genes were downregulated by tea polyphenols.…”
Section: Effects Of Polyphenols On Oxidative Stress and Inflammation mentioning
confidence: 99%
“…As long -term effects in chicken, tea polyphenols improved lipid metabolism and digestive enzymatic activities, and affected inflammatory status [35]. ECG supplementation significantly down-regulated the expression of fatty acid synthesis and β-oxidation/lipolysis genes [30]. They suggested that EGCG could alleviate fat deposition via the improved metabolism.…”
Section: Application Of Catechins For Veterinary Sciencementioning
confidence: 99%
“…These microorganisms include fungi (Rhizopus, Monascus, yeast, etc. ) and bacteria (mainly lactic acid bacteria, Bacillus, and acetic acid bacteria) (Wu et al, 2012;Li et al, 2015). For storage, Qu is predried in the sun (Fig.…”
Section: Introductionmentioning
confidence: 99%